2005
DOI: 10.1590/s1519-566x2005000300017
|View full text |Cite
|
Sign up to set email alerts
|

Ácaros (Acari) de dois sistemas de cultivo da seringueira no noroeste do estado de São Paulo

Abstract: -The cultivation of rubber trees (Hevea brasiliensis Muell. Agr.) has increased considerably in northwestern State of São Paulo. The objective of this work was to evaluate the mite fauna in two cultivation systems commonly found in this region, one in monocrop and other in which it is intercropped with "gariroba", Syagrus oleracea (Mart.) Becc. The study was conducted between May 2002 and April 2003, taking monthly samples of 150 leaflets of rubber tree of each plantation and 150 leaflets of gariroba. The faun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
25

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 11 publications
(18 reference statements)
2
22
0
25
Order By: Relevance
“…In Itiquira, in the state of Mato Grosso, Tanzini et al (2000) and Demite and Feres (2008) reported infestation by Hirsutella thompsonii Fisher on the mites Phyllocoptruta seringueirae Feres, 1998, C. heveae, and T. heveae. In the state of São Paulo H. thompsonii, has been observed infesting C. heveae mites collected on rubber trees (van der Geest et al, 2002;Bellini et al, 2005). In this work, one specimen of the predatory mite Agistemus sp.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In Itiquira, in the state of Mato Grosso, Tanzini et al (2000) and Demite and Feres (2008) reported infestation by Hirsutella thompsonii Fisher on the mites Phyllocoptruta seringueirae Feres, 1998, C. heveae, and T. heveae. In the state of São Paulo H. thompsonii, has been observed infesting C. heveae mites collected on rubber trees (van der Geest et al, 2002;Bellini et al, 2005). In this work, one specimen of the predatory mite Agistemus sp.…”
Section: Resultsmentioning
confidence: 80%
“…After the year 2000, T. heveae was reported a number of times as a pest of rubber trees (Pontier et al, 2000;Ferla and Moraes, 2002;Hernandes and Feres 2006a, b;Vis et al, 2006;Daud and Feres, 2007). In São Paulo, T. heveae is usually very numerous (Feres et al, 2002;Bellini et al, 2005;Hernandes and Feres, 2006a;Vis et al, 2006). This species inhabits mainly the abaxial surface of leaves and causes bronzing followed by premature leaf drop (Moraes and Flechtmann, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also obtained by Chiavegato (1986) studying Brevipalpus phoenicis Geijskes, 1939 (Tenuipalpidae) on citrus, which indicates that this stage is probably the most vulnerable to perishing in laboratory conditions. Another possible explanation for the high mortality during larval stage is the high moisture inside the trays (about 70%), since the peaks of infestation in the field were registered during the dry season, from April to May, in Southeastern and Northwestern parts of São Paulo and Southeastern Mato Grosso States (Feres et al 2002;Bellini et al 2005;Hernandes & Feres 2006a;Vis et al 2006;Daud & Feres 2007). Moreover, observed higher rates of survival of T. heveae when reared in opened trays than when in covered trays, resulting in a higher relative humidity on these latter trays.…”
Section: Discussionmentioning
confidence: 99%
“…This species goes through two nymphal stages before reaching adulthood, and the females had mean life expectancy of 28.5 days when reared on the clone PB 260 . Feres et al (2002), Bellini et al (2005), Hernandes & Feres (2006a) and Vis et al (2006), reported T. heveae as one the most abundant phytophagous mites on rubber tree crops in São Paulo State. Heavy infestations have also been registered (J. F. C. Benesi pers.…”
mentioning
confidence: 99%